Recent brachiopods from the southern Brazilian shelf: Palaeontological and biogeographical implications - Simoes, M.G.; Kowalewski, M.; Mello, L.H.C.; Rodland, D.L.; Carroll, M. (Palaeontology, 2004)
Until recently, the rhynchonelliform (articulated) brachiopod fauna from the Brazilian continental shelf (western South Atlantic) was represented only by the endemic species Bouchardia rosea (Mawe), reported from coastal waters of the states of São Paulo and Rio de Janeiro. The present study, based on samples from coastal (<30m), shelf, and continental slope waters (99-485 m), documents the South Atlantic brachiopod fauna and shows that this fauna is more widespread, diverse, and cosmopolitan than previously thought. Based on a total of 16,177 specimens, the following brachiopods have been identified: Bouchardia rosea (Family Bouchardiidae), Platidia anomioides (Family Platidiidae), Argyrotheca cf. cuneata (Family Megathyrididae), and Terebratulina sp. (Family Cancellothyrididae). In coastal settings, the fauna is overwhelmingly dominated by Bouchardia rosea. Rare juvenile (<2 mm) specimens of Argyrotheca cf. cuneata were also found at two shallow-water sites. In shelf settings (100-200 m), the fauna is more diverse and includes Bouchardia rosea, Terebratulina sp., Argyrotheca cf. cuneata, and Platidia anomioides. Notably, Bouchardia rosea was found in waters as deep as 485 m, extending the known bathymetric range of this genus. Also, the record of this brachiopod in waters of the state of Paraná is the southernmost known occurrence of this species. The genera Platidia and Terebratulina are documented here for the first time for the western South Atlantic. The Brazilian brachiopod fauna shares similarities with those from the Atlantic and Indian shelves of southern Africa, and from the Antarctic, Caribbean and Mediterranean waters. The present-day brachiopods of the western South Atlantic are much more cosmopolitan than previously thought and their Cenozoic palaeobiogeographic history has to be reconsidered from that perspective. © The Paleontological Association.
16 citations (Crossref) [2023-10-31]
Keywords: Argyrotheca; Argyrotheca cuneata; Atlantic Ocean; Bouchardia; Bouchardia rosea; Brachiopoda; Brazilian Shelf; Cancellothyrididae; Megathyrididae; Platidia; Platidia anomioides; Platidiidae; Recent; South-East Brazilian Bight; Terebratulida; Terebratulina; dept.esc; paleobiogeography

Occurrence and dispersal of magmas in the jurassic ferrar large igneous province, antarctica - Elliot, David H; Fleming, Thomas H (Gondwana Research, 2004)
Tholeiitic rocks of the Ferrar Large Igneous Province (FLIP) occur in a linear belt from the Theron Mountains to Horn Bluff in the Transantarctic Mountains and extend into southeastern Australasia. The FLIP was emplaced during the initial stages of Gondwana break-up from a source suggested to be in the proto-Weddell Sea region. Magma transport from its source (Weddell triple junction) was controlled by an Early Jurassic zone of extension. The FLIP comprises the Dufek intrusion, Ferrar Dolerite sills and dykes (sheet intrusions), and extrusive rocks consisting of pyroclastic strata overlain by Kirkpatrick Basalt lavas. The Dufek intrusion occurs in deformed supracrustal rocks of the foldbelt along the paleo-Pacific Gondwana margin. A few sills were emplaced in basement rocks, but the majority of the sheet intrusions occur in flat-lying Devonian to Triassic Beacon strata. Only in the central Transantarctic Mountains (CTM) and south and north Victoria Land (SVL, NVL) are extrusive rocks preserved overlying Beacon strata. The greatest cumulative thicknesses of magmatic rocks (ca. 2 km) occur in areas where lavas are preserved (CTM and SVL). Sheet intrusions have complex relationships. Dyke swarms (sensu stricto) are unknown and dykes cutting basement rocks are uncommon. Nevertheless, these dykes, including a 30-m-wide dyke in SVL, suggest that some magmas locally migrated up through basement rocks. In CTM and NVL the outcrop belt has a width of about 160 km. Sills originally extended farther toward the plate margin but have been cut out by erosion and Cenozoic faulting, most clearly in CTM; geophysical data suggest extension under the East Antarctic ice sheet for at least 100 km. Although Early Jurassic extension is documented in CTM, major rift-bounding faults have not been observed. Models for magma emplacement include transport along the axis of the Transantarctic Mountains and off-axis transport from major rift-bounding faults. Contrasts in geochemistry between lavas of NVL (MgO=6-7%) and CTM (MgO=2-4%) and the presence of massive dolerite bodies (CTM, SVL) suggest discrete episodes and locations of magma emplacement, and that there was no long range interconnection along the mountain range in supracrustal rocks.
108 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-968-850-538-745 tex.type: [object Object]
Keywords: Antarctica; Dispersal; Dyke; Ferrar; Gondwana; Jurassic; Magma; Sill; basement rock; continental breakup; dept.esc; emplacement; fold belt; large igneous province; magma; tholeiite

Colonization of a 'Lost world': encrustation patterns in modern subtropical brachiopod assemblages - Rodland, David L; Kowalewski, Michal; Carroll, Monica; Simoes, Marcello Guimaraes (Palaios, 2004)
The encrustation of Paleozoic rhynchonelliform brachiopods has been studied for decades, but modern brachiopods have not received similar scrutiny. The discovery of abundant subtropical brachiopods from the Southeast Brazilian Bight provides an unprecedented opportunity to assess epibiont abundance, diversity, and encrustation patterns in modern brachiopod assemblages. Across the outer shelf, encrustation frequencies vary among taxa, from mean values of 0.45% for Platidia to 9.3% for Argyrotheca. Encrustation frequencies for Bouchardia increase from 1.6% on the outer shelf to 84% on the inner shelf. Larger valves are encrusted more frequently, and epibionts preferentially colonize valve interiors. Increased encrustation on the inner shelf may reflect the greater surface areg of larger hosts, longer exposure of dead shells, water-mass characteristics, sedimentation rates, productivity, or other factors that vary with depth. Inner-shelf brachiopods exhibit encrustation frequencies comparable to those reported for epifaunal bivalves. The epibiont fauna is dominated by bryozoans and serpulids, with minor roles played by spirorbids, bivalves, barnacles, foraminifera, algae, and other taxa. Epibiont abundance at each site is highly variable, but sites are similar in rank importance of epibiont taxa. A different suite of epibionts colonized Paleozoic brachiopods, but similar patterns of encrustation have been observed, including preferential settlement according to valve morphology. These results provide a baseline for evaluating the encrustation of modern bivalves and ancient brachiopods, and may elucidate the macroevolutionary history of epibionts and their relationship to their hosts. © 2004, SEPM (Society for Sedimentary Geology).
43 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-264-058-710-061 tex.type: [object Object]
Keywords: Argyrotheca; Atlantic Ocean; Bivalvia; Bouchardia; Brachiopoda; Brazilian Shelf; Bryozoa; Foraminifera; Platidia; Thoracica; algae; brachiopod; continental shelf; dept.esc; encrustation; epibiont; species diversity

Abandoned underground storage tank location using fluxgate magnetic surveying: A case study - Van Biersel, Thomas P; Bristoll, Bill C; Taylor, Robert W; Rose, James (Ground Water Monitoring and Remediation, 2002)
In 1993, during the removal of a diesel and a gasoline underground storage tank at the municipal garage of the Village of Kohler, Sheboygan County, Wisconsin, soil testing revealed environmental contamination at the site. A site investigation revealed the possibility of a second on-site source of petroleum contamination. Limited historical data and the present usage of structures within the suspected source area precluded the use of most invasive sampling methods and most geophysical techniques. A fluxgate magnetometer survey, followed by confirmatory excavation, was conducted at the site. The fluxgate magnetometer survey identified nine possible magnetic anomalies within the 18 × 25 m area. The subsequent excavation near the anomalies revealed the presence of five paired and two individual 2000 L underground storage tanks. The fluxgate magnetometer survey, although affected by the proximity of buildings, was able to detect the buried tanks within 3 m of the brick structures, using a 1.5 × 1.5 m sampling array.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-308-736-083-041 tex.type: [object Object]
Keywords: Contamination; Excavation; Fuel storage; Fuel tanks; Groundwater pollution; Kohler; Magnetometers; Soil testing; Underground storage tanks; United States; Wisconsin; anomaly; dept.esc; magnetic survey; petroleum; site investigation; soil pollution; storage tank; underground storage

Physical volcanology and geological relationships of the jurassic ferrar large igneous province, antarctica - Elliot, David H; Fleming, Thomas H (Journal of Volcanology and Geothermal Research, 2008)
The Ferrar Large Igneous Province forms a linear belt for 3500 km along the Transantarctic Mountains, and as a geochemical province extends into southeastern Australasia. The principal components of the Ferrar are: intrusive - Ferrar Dolerite sills and dikes, and Dufek intrusion; pyroclastic - the Prebble, Mawson and Exposure Hill Formations; effusive - the Kirkpatrick Basalt. In terms of the three dimensional architecture of the Ferrar, a range of "facies" can be recognized in each of the principal components. The Ferrar province was initiated with a major episode of phreatomagmatism leading to formation of tephra cones and associated deposits, and near-surface vent structures. Activity switched to predominantly quiet effusion of alternating thick flood basalt flows and thin pahoehoe lobes and flows. Intrusive bodies were emplaced early, given the occurrence of dolerite clasts in tuff-breccias, but most sills were probably intruded after accumulation of extrusive rocks. Pre-existing rift structures played a major role in controlling the transport and distribution of the Ferrar magmas and the apparent centers of extrusive activity. The associated paleohydrology controlled the eruption styles. © 2008.
57 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/097-315-503-052-845 tex.type: [object Object]
Keywords: Antarctica; Basalt; East Antarctica; Ferrar; Ferrar Glacier; Flood basalt flows; Geochemistry; Geochronology; Jurassic; Magmas; Structural geology; Volcanic rocks; Volcanoes; Volcanology; dept.esc; flood basalt; large igneous province; magma; phreatomagmatism; pyroclastic deposit; tephra; volcanology